CONTRIBUTING FACTORS TO ENTREPRENEURIAL ATTRACTIVENESSE - Reggy N. Sarmita; Abraham Lelengboto (Faculty of Economics and Business, Universitas Klabat, 2020)
The purpose of this study was to find the contributing factors to entrepreneurial attractiveness. The methodology used in this study were quantitative and qualitative approach. Qualitative approach was used to identify the variables in this study, while the quantitative approach was used to group and categorize the variables into determined factors. Forty-four variables were generated from the interviews and furthermore were constructed into a set of questionnaires. The questionnaire was then distributed and filled out by 158 respondents. The findings of this study showed that there were 12 primary factors namely interest, social environment, opportunity, attitude, commitment, support of close person, financial need, wanting to be rich, networking, care, inspiration, and parents. These factors were recognized in this study as the contributing factors to entrepreneurial attractiveness. Keywords: Entrepreneurial Attractiveness, Interest, Social Environment, Opportunity